2014
DOI: 10.1590/s0102-86502014001800012
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound treatment for accelerating fracture healing of the distal radius. A control study

Abstract: PURPOSE:To investigate the accelerating effects of low-intensity pulse ultrasound stimulation (LIPUS) on the fracture healing of distal radius. METHODS:A total of 81 patients with distal radius fracture were randomly divided into two groups: the ultrasound treatment group and the control group. Patients in the ultrasound treatment group were immobilized in a below-elbow cast and received LIPUS treatment 15 min/day, while the control group were immobilized by a plaster support and cast. The patients were follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 27 publications
1
22
0
5
Order By: Relevance
“…The LIPUS treatment was used for 20 minutes a day except in 2 trials. [ 48 , 58 ] In one of these trials, [ 48 ] the LIPUS treatment was used for 15 minutes every day, and in the other one, [ 58 ] the LIPUS treatment was used 2 times a day for 20 minutes each. All of the included studies demonstrated good compliance with the LIPUS treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The LIPUS treatment was used for 20 minutes a day except in 2 trials. [ 48 , 58 ] In one of these trials, [ 48 ] the LIPUS treatment was used for 15 minutes every day, and in the other one, [ 58 ] the LIPUS treatment was used 2 times a day for 20 minutes each. All of the included studies demonstrated good compliance with the LIPUS treatment.…”
Section: Resultsmentioning
confidence: 99%
“…For the included trials, 5 trials [ 48 , 50 , 54 , 56 , 57 ] used the conservative treatment, and the conservative treatment for these 5 trials used plaster of Paris to maintain reduction. The plaster was not removed when LIPUS was used.…”
Section: Resultsmentioning
confidence: 99%
“…19 20 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 Two trials, Handolin and colleagues32 33 and Emami and colleagues,29 30 provided two publications reporting on the same group of patients. There were no shared patients between the TRUST pilot26 and the definitive trial 16.…”
Section: Resultsmentioning
confidence: 99%
“…All but two trials applied LIPUS for 20 minutes every day, either for a fixed period or until radiographic healing. Otherwise, one trial applied LIPUS for 15 minutes a day,36 and another trial for five minutes every second day 39. Fifteen trials (60%) provided their control group with an inactive device that was indistinguishable from the active LIPUS.…”
Section: Resultsmentioning
confidence: 99%
“…Nolte et al demonstrated that the healing rate for metatarsal fractures in patients treated with low‐intensity pulsed US was significantly faster than the healing rate for matched patients who were not treated. Liu et al found that low‐intensity pulsed US could promote fracture healing of the distal radius and promote local bone formation. Patel et al investigated the effects of low‐intensity pulsed US on the healing of mandibular fractures, and they found a significant improvement in radiographic density in the low‐intensity pulsed US treatment group compared to the control group.…”
Section: Discussionmentioning
confidence: 99%